Art of Our Time : The Saatchi Collection - 4. - Auping, Michael; Carlson, Prudence; Cooke, Lynne; Kramer, Hilton; Levin, Kim; Rosenthal, Mark; Tuchman, Phyllis; The Saatchi Gallery, London (London : Lund Humphries publishers ltd, 1984)
Bartlett, Jennifer ; Borofsky, Jonathan ; Jenney, Neil ; Longo, Robert ; Murray, Elizabeth ; Rothenberg, Susan ; Salle, David ; Sherman, Cindy ; Burton, Scott ; Shapiro, Joel ; Close, Chuck ; Fischl, Eric ; Golub, Leon ; Jensen, Bill ; Nutt, Jim ; Winters, Terry ; Clemente, Francesco ; Deacon, Richard ; Hodgkin, Howard ; Kossoff, Leon ; Scully, Sean ; Willing, Victor
biog. p. 11-12
Engels
boek